DOI: 10.11606/t.7.2004.tde-16102006-162026
|View full text |Cite
|
Sign up to set email alerts
|

Tradução para o português e validação de instrumento para triagem de pacientes em serviço de emergência: Canadian Triage and Acuity Scale (CTAS).

Abstract: A meus pais e irmãs pelo apoio incondicional, amor e compreensão demonstrados durante toda a minha vida e sobretudo durante a realização deste trabalho. A você, Maria AliceObrigada pelos ensinamentos transmitidos ao longo destes anos.Obrigada por respeitar minhas opiniões, limitações e sobretudo por acreditar em mim.Que você mantenha sempre a serenidade e humildade que lhe são peculiares. Podemos encerrar aqui uma relação acadêmica, mas espero que a relação de amizade e carinho perdure para sempre. Agradecimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
5

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
2
0
5
Order By: Relevance
“…These studies also include the validity and the reliability of the protocols in Pediatrics, and present instruments that contain reliable information to define care protocols that improve and broaden the practice of nurses. (10)(11)(12)(13)(14) The data are similar to another study (15) which found "almost perfect" agreement (Kappa = 0.884) between the complaint given at admission and the discharge medical diagnosis, indicating that the Canadian scale evaluated in this study represented a new instrument to be used in emergency services.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These studies also include the validity and the reliability of the protocols in Pediatrics, and present instruments that contain reliable information to define care protocols that improve and broaden the practice of nurses. (10)(11)(12)(13)(14) The data are similar to another study (15) which found "almost perfect" agreement (Kappa = 0.884) between the complaint given at admission and the discharge medical diagnosis, indicating that the Canadian scale evaluated in this study represented a new instrument to be used in emergency services.…”
Section: Discussionsupporting
confidence: 82%
“…(15)(16)(17) This also shows the importance of the triage for the care implementation, since it provides greater accessibility to emergency services, prioritizes the most serious cases, and is operative when the situation demands. It promotes a lower injury to users' health, since it facilitates the classification and orientation of the flow of patients, prioritizing the most serious patients in relation to the least severe ones.…”
Section: Discussionmentioning
confidence: 97%
“…Então, à medida que buscam os serviços de urgência e emergência, os usuários esperam receber um atendimento ideal: rápido, eficiente e eficaz. Nesse sentido, houve a necessidade de reestruturar o processo de trabalho e de redirecionamento da entrada dos usuários, que até então se baseava em uma forma de priorização por triagem, centrada na figura do coordenador médico e na lógica da exclusão [4][5][6].…”
Section: Introductionunclassified
“…As cinco categorias são: 1 -Risco imediato a vida (Avaliação médica imediata); 2 -Risco iminente a vida (avaliação médica em <10 min); 3-potencial risco de vida (Urgência) (avaliação médica em até 30 min); 4-Situação de potencial urgência ou de complicações/gravidade importante (atendimento médico em até 60 min); 5 -Menos urgente ou problemas clinico administrativos (avaliação médica em até 120 min) (HODGE, 2012;PIRES, 2003).…”
Section: Introductionunclassified
“…O Canadian Triage and Acuity Scale (Canadá) foi publicado em 1999, através da adaptação da escala Australiana para a realidade canadense e também consiste em cinco categorias: 1-Situações de risco a vida ou com sinais iminentes de risco de deterioração do quadro clinico; 2-Emergência; 3-Urgência; 4-Semi-urgência; e 5-Não urgência. (Pires, 2003;Bullard, 2014).…”
Section: Introductionunclassified